Do Mathematics and Reading Skills Impact Student Science Outcomes? - Doabler, Christian T.; Rojo, Megan; Gersib, Jenna A.; Fall, Anna-Maria; Longhi, Maria A.; Lovette, Gail E.; Roberts, Greg; Uy, Jasmine; Johnson, Katharina; Ghafghazi, Shadi; Phelps, Jason B.; Powell, Sarah R.; et al. (Journal of Learning Disabilities, 2025)
Establishing validated science programs for students with or at risk for learning disabilities requires testing treatment effects and exploring differential response patterns. This study explored whether students' initial mathematics and reading skills influenced their treatment response to a whole-class, second-grade science program called Scientific Explorers (Sci2). The original Sci2 study employed a cluster randomized controlled design and included 294 U.S. students from 18 second-grade classrooms. Differential effects of the program by initial mathematics and reading skill levels were not observed for an interactive science assessment and a distal science outcome measure. However, based on initial reading skill levels, moderation results were found on a science vocabulary measure, suggesting the effects of Sci2 were greatest for students with higher initial reading skills. Similar results were found using initial mathematics skill levels as a predictor of differential response such that students with higher mathematics skills reaped stronger treatment effects on the vocabulary measure. Further, we found initial mathematics skills also influenced outcomes on the proximal science content assessment, where students with higher initial mathematics skills led to higher outcomes. Overall, findings suggest Sci2 produced robust effects for all students (g = 0.24–1.23), regardless of initial skill proficiencies. Implications for exploring differential response in science intervention research are discussed.